Biogeographic distribution patterns and assembly processes of nirS‐type and nirK‐type denitrifiers across the black soil zone in Northeast China. Issue 6 (27th December 2021) - Hu, Xiaojing; Gu, Haidong; Liu, Junjie; Liu, Zhuxiu; Li, Lujun; Du, Shuli; Yu, Zhenhua; Li, Yansheng; Jin, Jian; Liu, Xiaobing; Wang, Guanghua
Abstract: Denitrifiers controlled the key‐step on global N cycles; however, little knowledge had been focused on their biogeography and associated underlying mechanisms. Here, based on high‐throughput sequencing, we investigated the nirS ‐type and nirK ‐type community diversity, biogeography, assembly mechanisms, and taxa interactions with 26 soil samples that were obtained across the black soil zone of northeast China. The results revealed that Proteobacteria was the unique known phylum of denitrifying bacteria, and Bradyrhizobium was the most abundant genus detected in both nirS ‐type and nirK ‐type denitrifiers across all soil samples. Compared with nirS ‐type denitrifiers, a relatively high cosmopolitan and community diversity were found in nirK ‐type. Those two types of denitrifying communities showed clear geographic distribution accompanied by obvious distance‐decay relationships. Variance partitioning analysis revealed that soil properties rather than sampling latitudes significantly influenced denitrifying communities with soil pH as the key drivers. However, stochastic processes, as dispersal limitation, played a greater role than deterministic processes in determining community assembly of both nirS ‐type and niK ‐type denitrifiers. This dispersal limitation was mostly contributed by the potential competition among taxa, with the negative interactions dominating in the denitrifying co‐occurrence patterns. Moreover, soil acidification with soil pH ranking from 4.0 to 4.5 simplified network structure and compelled denitrifiers to cooperate with each other in contrast to other soil pH ranges. These results provided comprehensive insights into the ecological processes of denitrifying communities, which were of great importance to the improvement of agricultural ecosystem services from the perspective of microorganisms. Core Ideas: The nirK ‐type denitrifiers were more cosmopolitan and diverse than nirS ‐type ones. Environmental heterogeneity mainly predicted the shifts of denitrifying communities. Soil pH primarily driving the assemblage of nirS‐ type and nirK‐ type denitrifiers. The nirS‐ type and nirK‐ type denitrifying communities were dominated by stochastic processes. Soil acidification resulted in strong cooperation among denitrifiers' taxa.